Reading for Academic Purposes: Problems Faced by Undergraduate Students of Visual Communication Design, University of Indraprasta PGRI - Elyza Martiarini (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
This study aimed at investigating reading for academic purposes problems of undergraduate students of Visual Communication Design at University of Indraprasta PGRI academic year 2016-2017 and to provide solutions to these problems. The target population included all undergraduate students of non-English department, studying at University of Indraprasta PGRI, and 78 students were taken as the object of this study. The data for this study were collected by questionnaire and readingtest. Qualitative data were analyzed by analysis content, while quantitative were processed by statistical program. The study found that the problems faced by the most students weretaking brief and relevant notes, understanding organization of text, paraphrasing by using own words, and understanding register words.